ERCP extraction of stones in situs inversus patients; state-of-the-art techniques - Deniz Gunsahin; Madalina Ilie; Oana Plotogea; Dan Nicolae Paduraru; Alexandra Bolocan; Octavian Andronic; Florentina Musat; Vlad Baleanu; Dragos Davitoiu; Mihai Pahomeanu; Bogdan Dumbrava; Vlad Enciu; et al. (Journal of Mind and Medical Sciences)
Situs inversus totalis (SIT) is a rare congenital disease that causes mirror transposition of the abdomino-thoracic structures. When such patients develop pathologies related to the bile duct, most commonly choledocholithiasis, the optimal diagnostic process can be hampered by the rarity of such a pathology and the lack of medical information on this topic. Once the diagnosis is established, through endoscopic ultrasound and MRCP, the patient is sent to perform ERCP, which requires tailored approaches for each case. We present the case of a 33-year-old patient who was previously documented with SIT. On admission she presented with abdominal pain and fever that started a week before presentation, so antibiotic therapy was initiated. Imaging investigations revealed intrahepatic gallstones, so she underwent ERCP the next day with the identification of an intrahepatic bile lake containing stones within. Naso-biliary drainage was placed and further 2 ERCP procedures followed, with the insertion of 3 plastic biliary stents. The evolution was favorable, until the complete removal of gallstones and remission of clinical symptoms. The patient was carefully monitored in the following two days and the stents were removed, being later discharged and monitored for a period of 6 months in which no biliary/digestive symptoms were noted.